1990
DOI: 10.1016/0165-2427(90)90064-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell activity of chicken intraepithelial leukocytes against rotavirus-infected target cells

Abstract: Intraepithelial leukocytes (IEL) and splenocytes collected from uninfected and rotavirus-infected chickens were evaluated for cytotoxic activity against a natural killer (NK) cell-susceptible lymphoblastoid cell line (LSCC-RP9) and against rotavirus-infected chick kidney cells in 4-h chromium-release assays. Both splenocytes and IELs from uninfected and rotavirus-infected chickens were cytotoxic for LSCC-RP9, and the levels of this NK cell activity were not altered by infection of the host with rotavirus. IELs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Paradoxically, chickens and turkeys were more susceptible to experimental disease with RV in older ages (56 to 119 days) than birds in first few weeks of life (Yason & Schat 1986b, 1987. However, in field situation, evidence indicates that most of turkeys and chickens will have been infected, and presumably will have developed some immunity, well before this age (Myers & Schat 1990a, 1990b). Added to this, Jones et al (1979) reported lack of age resistance to disease as well as an outbreak of rotaviral diarrhea that occurred between 32 and 92 weeks of age in commercial laying hens.…”
Section: Host Rangementioning
confidence: 99%
See 2 more Smart Citations
“…Paradoxically, chickens and turkeys were more susceptible to experimental disease with RV in older ages (56 to 119 days) than birds in first few weeks of life (Yason & Schat 1986b, 1987. However, in field situation, evidence indicates that most of turkeys and chickens will have been infected, and presumably will have developed some immunity, well before this age (Myers & Schat 1990a, 1990b). Added to this, Jones et al (1979) reported lack of age resistance to disease as well as an outbreak of rotaviral diarrhea that occurred between 32 and 92 weeks of age in commercial laying hens.…”
Section: Host Rangementioning
confidence: 99%
“…Rotavirus specific IgM, IgG and IgA were detected in serum where intestinal antibody response entirely consisted of IgA (Figure 3). Myers and Schat (1990a), as an important in vivo immune response, demonstrated NK cell activity in chick intra-epithelial leukocytes against RVs. Myers and Schat (1990b) further reported that intestinal antibodies (IgA) alone are not only a mediator for recovering from disease, but also must regarded as development of resistance to re-disease.…”
Section: Active Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results fi'om Chai and Lillehoj's study (1988) revealed the NK cell activity of chicken i-IEL against tumor cells was greater in the jejunum than in the duodenum. However, Myers and Schat (1990b) did not observe any difference in NK cell activity of chicken i-IEL collected from the duodenum or the jejunum.…”
Section: Intraepithelial Lymphocytesmentioning
confidence: 93%
“…The NK cell cytotoxicity of chicken i-EEL against chicken tumor cells has been demonstrated by . Myers and Schat (1990b) have demonstrated the NK cell activity of chicken ilEL against rotavirus-infected target cells. In this study, it was suggested that NK cell activity of i-IEL may be an important immune response to rotavirus infection in vivo.…”
Section: Intraepithelial Lymphocytesmentioning
confidence: 99%